Industrial Training Report: Universiti Sultan Zainal Abidin (UniSZA) Library, Gong Badak Campus / Che Wan Karmila Che Wan Ahmad - Che Wan Ahmad, Che Wan Karmila (Faculty of Information Management, 2019)
Library profession is specialized and technical in nature and so industrial training for the library science students must have both the elements of theory and practical skills incorporated. The industrial training is the student learns, practice and exposes the real working environment. Industrial training can be known as practical training. From practical training, student also learns about the ability to working under pressure, work ethics, and demands of the organization. Usually, practical training has supervision from the staff of the organization. In order to fulfil the requirements of IM 244 program, this training is requirement from the University Technology MARA (UiTM) for student of final year in Bachelor of lnformation Science (Hons.) Library Management. This paper will present about industrial training at Library of Universiti Sultan Zainal Abidin (UniSZA) Campus Gong Badak, Kuala Terengganu that have been approved by the Office of Registration of Universiti Sultan Zainal Abidin (UniSZA). Student must undergo and carried out this industrial training for five months, started from 03 February 2019 until 30 June 2019.